MODEL KESEIMBANGAN HUBUNGAN PENGARUH ANTARATINGKAT BUNGA, LAJU INFLASI, DAN KURS VALUTA ASING - Endang Setyowati; Algifari Algifari (Fakultas Bisnis UKDW, 2017)
The aims of this research is to develop unequilibrium model relationship among interest rate,inflation, and foreign exchange rate in Indonesia using monthly data from January 2011 to April2015. The results of Augmented Dickey-Fuller test shows that the data of interest rate, inflation, andforeign exchange rate in this period is not stationary at level, but stationary in first difference.Johansen Cointegration test results indicate that the interest rate, inflation, and foreign exchange rateare cointegrated. Equilibrium model that used to determine the relationship among interest rate,inflation, and foreign exchange rate is Vector Error Correction models. The results of this studyindicate that interest rate affect on inflation and foreign exchange rate in Indonesia.Keyword: Interest Rate, Inflation, Exchange Rate,Vector Error Correction Model